ANALISIS YURIDIS KEBIJAKAN PEMIDANAAN DENGAN HUKUMAN KEBIRI TERHADAP PELAKU PEDOFILIA - Muhammad Andi Dirgantara; Syafruddin Kalo; Alvi Syahrin; Chairul Bariah (Universitas Sumatera Utara, 2017)
ABSTRACT Sentencing policy with castration punishment is a form of government efforts to suppress the sexual abuse of children were recently increased. Award gelding punishment for pedophiles do with chemical castration. objects that are discussed in this study is to answer the question about the policy of punishment for pedophiles in Indonesian positive law, setting penalties gelding by Perppu No. 1 2016 on the Second Amendment Act No. 23 of 2002 on Protection of Children and penalties gelding in the perspective of Islamic law and human rights, this research then produced several conclusions that pedophilia is a disorder of sex deviates experienced by adults the sexual attraction to children that lead to rape and / or sexual abuse, perpetrators be punished gelding was ever convicted offenders with similar criminal offense and punishable by life imprisonment or imprisonment of at least 10 (ten) years. in Islamic law does not use neuter punishment for perpetrators of rape or sexual abuse and differences of opinion against punitive castration for pedophiles rights terms manusia.Berdasarkan conclusions obtained in this study, it is suggested not only add to the type and weight penalties for pedophiles but also consider the interests of children who are victims of sexual violence, the perpetrators were never convicted the same and has serious impacts should be put to death without punishment made a gelding and reviewing punitive castration for pedophiles. Keywords: Policy Punishment, Punishment gelding, Actors Pedophilia